the development of the strength characteristic of speed and its role in the effectiveness of the shooting from jump in basketball according to the proposed alternative training program in a low-intensity for young players - baffa abdellah (sports creativity, 2025)
Abstract: share to know the evolution of the strength characteristic of speed and its role in the effectiveness of the shooting from jump in basketball and this after the application of a set of training courses according to the proposed alternative training program in a low-intensity on a group composed of two youngs teams of basketball in the city of Laghouat, The estimated 12 players from each team were randomly chosen. We have also adopted in the treatment of the problem of research on the alternative training program in low-intensity using the experimental method through vertical jump tests horizontal jump and also to test the shooting from jump After the statistical processing and data collection, the results showed that the proposed training program for the development of strength characteristic of speed was a positive factor in improving the effectiveness of the shooting from jump in basketball. In the light of previous results, we recommend to use experimental methods studies on other groups and using other methods of sports training